APLIKASI UNTUK IDENTIFIKASI SHORT MESSAGE SERVICE (SMS) SPAM BERBASIS ANDROID - , ZAID ROMEGAR MAIR; , Dr. Techn. Ahmad Ashari, M.I.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of smartphones as a communication technology that is cheap, easy and fast, is often used by some people who are not responsible for committing crimes through SMS. Rampant fraud through SMS may cause crime in the form of SMS spam, so in this study constructed a system of web-based tool to conduct analysis on smartphone android to identify categorization of SMS, which is implemented using Naive Bayessian Filtering algorithm for determining the value of the probability SMS contents of the smartphone Android Samsung Galaxy Young Kernel NAND. The method used is a forensic process model, which consists of the maintenance Preservation, Acquisition, Examination, Analysis and Reporting. Data were collected by means extraction messages from internal memory (ROM) of Android phones using AFLogical-OSE tool by selecting the data stored in the / mnt / sdcard / forensics and then transferred to a computer via a data cable. Based on the results of research conducted tests on 65 types of sms, 43 sms, identified as spam and 22 sms identified as not spam. Data analysis approach word (n-grammar) of the obtained results are mostly spam.